2007
DOI: 10.1097/01.tp.0000261711.08833.a1
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Corneal Transplantation in the Miniature Pig: Efficacy of Immunosuppressive Treatment

Abstract: Corneal allograft rejection is frequently studied in small rodent or rabbit models. To study mechanisms of rejection in a model that more closely mimics transplantation in humans, we performed orthotopic corneal transplantation in the miniature pig using a 7-mm diameter donor graft. Four groups of recipients were studied: 1) untreated naive, 2) untreated vascularized (high risk), 3) high-risk grafts treated by topical application of prednisolone, or 4) high-risk grafts treated with a combined systemic immunosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…10 Williams et al also reported a higher incidence of rejection than we achieved in an outbred sheep model, but their graft size was relatively larger. 9 Increasing graft size (from 7 to 8 or 9 mm) or, alternatively, pre-vascularization of the recipient cornea 10 would be likely to increase the incidence of rejection in this model.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…10 Williams et al also reported a higher incidence of rejection than we achieved in an outbred sheep model, but their graft size was relatively larger. 9 Increasing graft size (from 7 to 8 or 9 mm) or, alternatively, pre-vascularization of the recipient cornea 10 would be likely to increase the incidence of rejection in this model.…”
Section: Discussionmentioning
confidence: 71%
“…However, as in the rat, rabbit corneal endothelial cells can proliferate, restoring the clarity of a graft after rejection. Cat models, in which corneal endothelial cells essentially are amitotic in vivo, 8 and, more recently, sheep and outbred pig models have been reported, 9,10 where sheep have been used successfully to test the effect on rejection following transduction of the cornea with cytokine genes. 11 However, the supply of reagents for immunological studies in cats and sheep is limited compared to pigs, and no inbred strains are available.…”
mentioning
confidence: 99%
“…Corneal allografts from inbred miniature pigs transplanted to outbred pigs has shown promise as large eye model to study topical and systemic immunosuppressive therapy (Tavandzi et al, 2007; Nicholls et al, 2012) to prevent corneal allograft rejection in humans as compared to other large eye models (Van Horn et al ., 1977; Williams et al, 1999). The similarities in corneal morphology between miniature and domestic swine found in the present study, as well as with the human corneal morphology, with the exception of Bowman’s layer, further support the miniature pig as a useful tool to model corneal graft transplantation and allograft rejection therapies in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporin A is used systemically for high-risk human corneal allografts with limited success, and concerns over its side-effects restrict wider use. Systemic cyclosporin is only moderately effective in preventing corneal rejection when given in conjunction with other immunosuppressive drugs in a high-risk pig model [8], but has shown some promise administered in a subconjunctival silicone implant [17]. Newer immunosuppressive agents have also been used topically in an attempt to delay or prevent corneal allograft rejection.…”
Section: Chemokines Antigen Presentation and Neovascularizationmentioning
confidence: 99%